An explicit coupled MPM formulation to simulate penetration problems in soils using quadrilateral elements. (May 2022) - Martinelli, Mario; Galavi, Vahid
Abstract: This paper describes an MPM formulation using linear quadrilateral elements suitable for soil-structure-interaction problems. The volumetric locking and stress-oscillations are mitigated using a reduced integration technique and the Gauss integration scheme, respectively. The formulation can be used with both structured and unstructured computational meshes. In addition, an improved calculation scheme is proposed to obtain accurate contact reaction forces, especially for contacts between non-porous structures and soils with high liquid pressures. The formulation is validated by simulating a wide range of applications such as a water dam break, 1D large-strain consolidation, and the bearing capacity of a strip footing. Finally, the installation of a cone penetrometer in a centrifuge is successfully simulated in soft soils and compared with the experimental data for the entire range of drainage conditions.